Characterization of the Dual Functions of LvCrustinVII from Litopenaeus vannamei as Antimicrobial Peptide and Opsonin - Jie Hu; Shihao Li; Qian Lv; Miao Miao; Xuechun Li; Fuhua Li (Marine Drugs, 2022)
Crustin are a family of antimicrobial peptides that play an important role in protecting against pathogens infection in the innate immune system of crustaceans. Previously, we identified several novel types of crustins, including type VI and type VII crustins. However, their immune functions were still unclear. In the present study, the immune function of type VII crustin LvCrustinVII were investigated in Litopenaeus vannamei. LvCrustinVII was wildly expressed in all tested tissues, with relatively high expression levels in hepatopancreas, epidermis and lymphoid organ. Upon Vibrio parahaemolyticus infection, LvCrustinVII was significantly upregulated in hepatopancreas. Recombinant LvCrustinVII (rLvCrustinVII) showed strong inhibitory activities against Gram-negative bacteria Vibrio harveyi and V. parahaemolyticus, while weak activities against the Gram-positive bacteria Staphylococcus aureus. Binding assay showed that rLvCrustinVII could bind strongly to V. harveyi and V. parahaemolyticus, as well as the cell wall components Glu, LPS and PGN. In the presence of Ca2+, rLvCrustinVII could agglutinate V. parahaemolyticus and enhance hemocyte phagocytosis. The present data partially illustrate the immune function of LvCrustinVII, which enrich our understanding on the functional mechanisms of crustins and provide useful information for application of this kind of antimicrobial peptides.